Field-of-view optimization of magnetically actuated 2D gimballed scanners - Gökdel, Yiğit Dağhan; Aköz, Gökçe (Tubitak Scientific & Technical Research Council Turkey, 2020)
This work presents the field of view (FOV) maximization of a magnetically actuated two-dimensional (2D) gimballed scanner. The process of maximization is completed in two steps. (1) Optimization of the electrocoil providing the magnetic force that moves the scanner and (2) precise choice of optimum respective locations of both the scanner and the electrocoil. We first derived a formula relating the generated magnetic flux density, coil design parameters and driving voltage. Subsequently, we discussed the design trade-offs of an actuating electrocoil. We also conducted several experiments on a stainless steel 430 scanner having a footprint of 15 mm x 15 mm and a thickness of 460 mu m. We determined the precise locations for the system components producing the maximum total optical scan angle (TOSA) hence the largest FOV. Finally, we proposed an empirically demonstrated formula, p(x(1), y(1)) approximate to p(0.25L(s) + 0.25L(m)), for the optimum electrocoil location with respect to the scanner by providing an offset Delta x and Delta y from the center to be able to successfully maximize the displacement and the related total optical scan angle of the system.
15 pages
Keywords: Microscanner; Magnetic actuation scheme; Electrocoil; Total optical scan angle (TOSA); Field of view (FOV); Experimental optimization